Introduction of rugby-5 in an educational process on physical education at secondary school - Подоляка [Oleg Podolyaka], Олег Борисович; Мартиросян [Artur Martirosyan], Артур Артурович; Філенко [Igor Filenko], Ігор Юрійович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> Facilities of introduction are considered in the educational process of schoolchildren of 10th years of age of rugby-5 within the framework of lessons on physical education. Ways of physical education of schoolboys are indicated. Technical and tactical elements of game is considered in rugby-5. Facilities and methods of studies of schoolchildren of secondary forms for the sporting and outdoor games. The high level of the personal interest of students is established to engagement in rugby-5. In research 32 schoolchildren of 5th forms took part aged 10–11 years. Efficiency of the use of informative facilities of introduction of rugby-5 in the educational process of schoolchildren of secondary school is proved. <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->